2008
DOI: 10.1542/peds.2007-1243
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Medical and Dental Health, Access to Care, and Use of Services in US Children

Abstract: BACKGROUND. Not enough is known about the national prevalence of racial/ethnic disparities in children's medical and dental care. OBJECTIVE. The purpose of this work was to examine racial/ethnic disparities in medical and oral health, access to care, and use of services in a national sample. METHODS. The National Survey of Children's Health was a telephone survey in 2003–2004 of a national random sample of parents and guardians of 102353 children 0 to 17 years old. Disparities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
340
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 440 publications
(373 citation statements)
references
References 26 publications
20
340
2
1
Order By: Relevance
“…LPIs have higher odds of severe impairment, and those who [22][23][24][25][26][27] Non-Englishspeaking families also tend to have reduced access to and utilization of high-quality pediatric health care, which identifies and helps with the effects of adverse physical and environmental exposures. 28,29 Our results expand on the current literature in several ways. With this cohort, we were able to follow participants from infancy to school age and find deficiencies in LPIs compared with FTIs at 2 time points.…”
Section: Discussionsupporting
confidence: 84%
“…LPIs have higher odds of severe impairment, and those who [22][23][24][25][26][27] Non-Englishspeaking families also tend to have reduced access to and utilization of high-quality pediatric health care, which identifies and helps with the effects of adverse physical and environmental exposures. 28,29 Our results expand on the current literature in several ways. With this cohort, we were able to follow participants from infancy to school age and find deficiencies in LPIs compared with FTIs at 2 time points.…”
Section: Discussionsupporting
confidence: 84%
“…A study in adult mental health care found a greater disparity in racial and ethnic minorities' access to psychiatrists compared with other providers, 38 and pediatric studies have concluded that disadvantaged groups less frequently see specialists or use prescription medications. 25,[39][40][41][42][43][44] This study has some limitations. Likewise, the extent of management by providers and the depth of discussion at PCP visits could not be determined.…”
Section: Discussionmentioning
confidence: 95%
“…9 Disparities in the well-being of children in the United States are growing. [10][11][12][13] These racial, ethnic, gender, and class-based disparities have profound implications for the welfare of children in the United States and for the adults they will become. [14][15][16][17][18][19] The sources of these disparities are deeply rooted in inequities in social and environmental determinants of health (eg, poverty, income inequality, maldistribution of educational and other resources, racism, and environmental injustice) and the failure of public policies to address them.…”
Section: Background Informationmentioning
confidence: 99%